Quantitative analysis of artificial sweeteners in soft drink samples - Meghla, Yashna Tahjib (BRAC Univeristy, 2018)
This thesis is submitted in partial fulfilment of the requirements for the degree of Bachelor of Science in Biotechnology, 2018.